PREDIKSI FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Iwan Kusuma Negara (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This study aims to predict financial distress on insurance companies listed on the Indonesia Stock Exchange period 2011-2016. Type of research used in this research is descriptive research. Sampling technique in this research using purposive sampling technique. Data collection method in this research is sample survey method. Data collection techniques using documentation techniques. Data analysis technique using Altman Z-Score model with formula Z = 1,2X1 + 1,4X2 + 3,3X3 + 0,6X4 + 1,0X5. The results showed that in the period 2011 there were 2 companies in the category of distress area and 7 companies in the grey area category. In the period 2012 and 2013 there were 3 companies in the category of distress area, 5 companies in the grey area category and 1 company in the category of non-distress area. In the period 2014 there were 5 companies in the category of distress area, 2 companies in the grey area category and 2 companies in the category of non-distress area. In the period 2015 there were 6 companies in the category of distress area, 1 company in the grey area category and 2 companies in the category of non-distress area. And in the period 2016 there were 4 companies in the category distress area, 4 companies in the grey area category and 1 company in the category of no distress area.Keywords : Prediction, Z-Score, Financial Distress, Insurance Companies, Bankruptcy